Adaptação de um Índice de Integridade Biótica (IIB) com peixes de riachos do Alto Rio Sorocaba (SP). - Viana, Mariana (2018)
A biological monitoring program using a Index of Biotic Integrity (IBI) in the Alto Sorocaba Basin will be efficient for quick evaluations, cost-effective, and analysis efficiency, and may assist in public power decision-making in directing of efforts to conserve the aquatic biota and to identify and minimize the physical habitat losses of the streams in the region. This work aimed to adapt a integrity biotic index (IBI) for the streams of the Alto Rio Sorocaba sub-basin. In the region of study is located the main source of the Metropolitan Region of Sorocaba (RMS), the reservoir of Itupararanga. Measurements of environmental characteristics and fish collections were carried out in 8 streams. Fish communities were analyzed using 27 biotic variables related to composition, diversity, trophic structure and habitat use. The biotic variables were selected concerning range, responsiveness and redundancy. A physical habitat index (IFH) was used to evaluate environmental characteristics. The IFH was elaborated from the variables: substrate stability, speed and depth variability, flow stability, sample pool, runs and riffles, vegetation cover and bank stability. The IBI was validated using PHI correlation significance. From 27 biotic variables tested, four were selected: siluriform richness proportion, siluriform individuals proportion number, omnivorous individuals proportion number and trophic categories number. These measures represent the abundance, species diversity and trophic structure, not expressing species composition and habitat use, which is a limiting factor to the use of the index to obtain more comprehensive results about the environments. No stream was rated as excellent and none as without fish. Fifty percent of the streams were classified as regular and 37.5% in the good category, demonstrating that many streams can still be used as reference. Despite its limitations, the adapted IBI is a useful tool for future biological monitoring and long-term biodiversity conservation and at low cost.